When organizations are too good: Applying Aristotle's doctrine of the mean to the corporate ethical virtues model. (22nd February 2017) - Kaptein, Muel
Abstract: Aristotle's doctrine of the mean states that a virtue is the mean state between two vices: a deficient and an excessive one. The Corporate Ethical Virtues (CEV) Model defines the mean and the corresponding deficient vice for each of its seven virtues. This paper defines for each of these virtues the corresponding excessive vice and explores why organizations characterized by these excessive vices increase the likelihood that their employees will behave unethically. The excessive vices are patronization, pompousness, lavishness, zealotry, overexposure, talkativeness, and oppressiveness.